Tracking of magnetite labeled nanoparticles in the rat brain using MRI. - Naira P Martínez Vera; Reinhold Schmidt; Klaus Langer; Iavor Zlatev; Robert Wronski; Ewald Auer; Daniel Havas; Manfred Windisch; Hagen von Briesen; Sylvia Wagner; Julia Stab; Motti Deutsch; et al. (PLoS ONE)
This study was performed to explore the feasibility of tracing nanoparticles for drug transport in the healthy rat brain with a clinical MRI scanner. Phantom studies were performed to assess the R1 ( =  1/T1) relaxivity of different magnetically labeled nanoparticle (MLNP) formulations that were based on biodegradable human serum albumin and that were labeled with magnetite of different size. In vivo MRI measurements in 26 rats were done at 3T to study the effect and dynamics of MLNP uptake in the rat brain and body. In the brain, MLNPs induced T1 changes were quantitatively assessed by T1 relaxation time mapping in vivo and compared to post-mortem results from fluorescence imaging. Following intravenous injection of MLNPs, a visible MLNP uptake was seen in the liver and spleen while no visual effect was seen in the brain. However a histogram analysis of T1 changes in the brain demonstrated global and diffuse presence of MLNPs. The magnitude of these T1 changes scaled with post-mortem fluorescence intensity. This study demonstrates the feasibility of tracking even small amounts of magnetite labeled NPs with a sensitive histogram technique in the brain of a living rodent.